Perianal Merkel cell carcinoma - a rare case report - B A, Arifin; Sainal, Mohd. Yusof; Elagili, Faisal; Md Nor, Azmi (2022)
INTRODUCTION Merkel cell carcinoma is a rare, aggressive neuroendocrine skin cancer that primarily affects elderly men in sun-exposed areas such as the extremities. To the best of our knowledge, this is the first case of a perianal MCC. OBJECTIVE We present a young male with perianal Merkel cell carcinoma. CASE REPORT A previously healthy 35-year-old man presented with left perianal a mass. Initially, his symptoms were attributed to a cold perianal abscess. He was referred to our center due to persistent swelling. The mass was 4x4cm in size and 3cm away from the anal verge; it was firm, nontender and not mobile in relation to the underlying musculature; it grew rapidly and ulcerated in a few weeks. Following biopsies of the lesion, it was discovered to be a neuroendocrine carcinoma that stained CK20- positive, indicating it was a Merkel cell carcinoma. A thorough metastatic work-up, which included a chest x-ray, CT scan, and MRI, revealed evidence of widespread metastatic disease. A multidisciplinary team meeting was held to discuss the case, and palliative chemoradiotherapy was scheduled for the patient. However, he died before receiving palliative care. CONCLUSION MCC is a rare, aggressive carcinoma that typically appears in areas that are exposed to the sun. A colorectal surgeon should consider MCC as a differential diagnosis when faced with a rapidly growing, painless lesion in the perianal region. Early detection and treatment may lead to a higher rate of patient survival. However, because MCC is uncommon, more research is required to develop treatment protocols for metastatic disease.